State-public administration of education as the main direction of democratization - Inna Shorobura (Kazimierz Wielki University, 2020)
Public administration of the education system is a productive activity of the society, which contains an active manifestation of civic position, social initiative and social responsibility in the management of the education system.The purpose of the article is to emphasize the issues of state-public administration of education as the main direction of democratization in the field of education. There are three levels of state administration in the educational sphere: the national level; regional level; district level.